Allergic disease and sensitization disparity in urban and rural China: A EuroPrevall‐INCO study. Issue 12 (21st December 2022) - Fu, Wanyi; Zheng, Zhenyu; Zhao, Jiefeng; Feng, Mulin; Xian, Mo; Wei, Nili; Qin, Rundong; Xing, Yuhan; Yang, Zhaowei; Wong, Gary W. K.; Li, Jing
Abstract: Background: Studies in comparison with allergic diseases and sensitization between rural and urban environments in westernized countries might be biased and not adequately reflect countries undergoing rapid transition. Methods: A total of 5542 schoolchildren from urban area and 5139 from rural area were recruited for the EuroPrevall‐INCO survey. A subsequent case–control sample with 196 children from urban area and 202 from rural area was recruited for a detailed face‐to‐face questionnaire and assessment of sensitization. Skin prick tests and serum‐specific IgE measurements were used to assess sensitizations against food and aeroallergens. Logistic regression analysis was used to determine associations between risk/protective factors, food adverse reactions (FAR), allergic diseases, and sensitizations. Results: Prevalence of self‐reported allergic diseases, including asthma (6.6% vs.2.5%), rhinitis (23.2% vs.5.3%), and eczema (34.1% vs.25.9%), was higher in urban than in rural children. Urban children had a significantly higher prevalence of FAR and related allergic diseases, and lower food/inhalation allergen sensitization rate, than those of rural children. In urban children, frequent changing places of residency (odds ratio 2.85, 95% confidence interval: 1.45–5.81) and antibiotic usage (3.54, 1.77–7.32) in early life were risk factors for sensitization, while sensitization and family history of allergy were risk factors for allergic diseases. In rural children, exposure to rural environments in early life was protective against both allergen sensitizations (0.46, 0.21–0.96) and allergic diseases (0.03, 0.002–0.19). Conclusion: We observed a disparity in rates of allergic diseases and allergen sensitization between rural and urban children. In addition to family history, the development of allergic diseases and allergen sensitization were associated with specific urban/rural environmental exposures in early life.